Use of a web‐based portal to return normal individual research results in Early Check: Exploring user behaviors and attitudes. Issue 6 (23rd March 2023) - Cope, Heidi; Lincoln‐Boyea, Beth; Gwaltney, Angela You; Biesecker, Barbara B.; Moultrie, Rebecca; Alexander, Amir A.; King, Nancy M. P.; Check, Jennifer; Corbo, Allyson; Tzeng, Janice; Porter, Katherine Ackerman; Peay, Holly L.
Abstract: Early Check is a voluntary, large‐scale expanded newborn screening study in North Carolina that uses a self‐directed web‐based portal for return of normal individual research results (IRR). Little is known about participant perspectives in using web‐based portals to receive IRR. This study explored user attitudes and behaviors within the Early Check portal using three methods: (1) a feedback survey available to the consenting parent of participating infants (typically mothers), (2) semi‐structured interviews conducted with a subset of parents, and (3) Google Analytics. During an approximate 3‐year period, 17 936 newborns received normal IRR and there were 27 812 visits to the portal. Most surveyed parents reported viewing their baby's results (86%, 1410/1639). Parents largely found the portal easy to use to get results, and helpful in understanding the results. However, 10% of parents said it was difficult to find enough information to understand their baby's results. In Early Check, providing normal IRR via the portal made a large‐scale study practical, and was highly rated by most users. Return of normal IRR may be particularly amenable to web‐based portals, as the consequences to participants from not viewing results are modest, and the interpretation of a normal result is relatively straightforward. Abstract :